2022
DOI: 10.3390/d15010012
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Carbon Sequestration of Seaweed in the Ma’an Archipelago, China

Abstract: Seaweed communities perform a variety of ecological services, including primary productivity supply, biological habitat construction, water purification, and acting as marine carbon sinks. The abundance of seaweed is the basis for the assessment of ecological services in communities. The Ma’an Archipelago, adjacent to the Yangtze River estuary in China, is an important and typical island group. In this study, the abundance of seaweed in the typical coastal islands of the Ma’an Archipelago, Zhejiang Province, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…According to the conversion ratio of wet to dry weight, the ratio of dry to wet weight of Sargassum thunbergii is about 0.57 [45], and the ratio of dry to wet weight of Ulva pertusa is about 0.19 [46]. Based on this, it can be concluded that the dry weight of Gouqi Island intertidal Sargassum thunbergii is about 8.0 × 10 8 g, and the dry weight of Ulva pertusa is about 6.6 × 10 7 g. The carbon sequestration of Sargassum thunbergii accounts for approximately 0.30 of the dry weight, while Ulva pertusa accounts for approximately 0.29 of the dry weight [47]. Therefore, the carbon sequestration capacity of Gouqi Island intertidal Sargassum thunbergii is 2.4 × 10 8 g, and the carbon sequestration capacity of Ulva pertusa is 1.9 × 10 7 g. The satellite imaging time is in summer, during the maturation and decline period of the intertidal seaweed on Gouqi Island.…”
Section: Carbon Sequestration Of Seaweed In the Intertidal Zone Of Go...mentioning
confidence: 77%
“…According to the conversion ratio of wet to dry weight, the ratio of dry to wet weight of Sargassum thunbergii is about 0.57 [45], and the ratio of dry to wet weight of Ulva pertusa is about 0.19 [46]. Based on this, it can be concluded that the dry weight of Gouqi Island intertidal Sargassum thunbergii is about 8.0 × 10 8 g, and the dry weight of Ulva pertusa is about 6.6 × 10 7 g. The carbon sequestration of Sargassum thunbergii accounts for approximately 0.30 of the dry weight, while Ulva pertusa accounts for approximately 0.29 of the dry weight [47]. Therefore, the carbon sequestration capacity of Gouqi Island intertidal Sargassum thunbergii is 2.4 × 10 8 g, and the carbon sequestration capacity of Ulva pertusa is 1.9 × 10 7 g. The satellite imaging time is in summer, during the maturation and decline period of the intertidal seaweed on Gouqi Island.…”
Section: Carbon Sequestration Of Seaweed In the Intertidal Zone Of Go...mentioning
confidence: 77%